From postcolonial social contract to the arab uprisings: the neoliberal transformation of the state–society relations and the alternative spaces of the new political activism - BELDER, FERİT (My University, 2023)
The Arab Uprisings have indelibly impacted the lives of people across the Arab world. Despite many movements facing major disappointments after more than one decade, the material and ideational aspects of the uprisings provide a satisfactory analysis of one of the most significant moments in the history of the region. This article focuses on the political-economic roots of the Arab Uprisings to see the gradual decline in regime security and the breakdown of the postcolonial social contract. It also takes the remarkable role of information technology in shaping new political actorness that managed to combine old and new methods of resistance and in broadening the sphere of political interaction without absolute control of the regimes. Within this context, it is organized as follows. First, it makes sense of the transformation of the state and the state–society relations within the neoliberal reformulation of politics. Second, it reveals the politics of the governed to see alternative forms of politics, solidarity, and information networks. Third, it examines the neoliberal reforms in the Arab world with specific respect to Egypt to see how the state undertook a structural change that eventually undermined the existing social contract which was at the base of the legitimacy. Lastly, the role of the Internet on the politics of the governed in times of political-economic crisis of the state is analyzed. It is argued that the neoliberal transformation of state-society relations and the alternative spaces of political activism both provide a comprehensive outlook to explain the Arab Uprisings.

Arap Ayaklanmaları, Arap dünyasında insanların yaşamlarını kalıcı bir şekilde etkilemiştir. On yılı aşkın süre sonrasında her ne kadar pek çok hareket ciddi hayal kırıklıkları yaşamış olsa da ayaklanmaların maddi ve düşünsel yönleri bölge tarihinin bu en önemli anlarından birine tatmin edici analizler sunmaktadır. Bu çalışma, rejim güvenliğinin kademeli gerileyişi ve post-kolonyal toplumsal sözleşmenin bozuluşuna bakmak için Arap ayaklanmalarının politik-ekonomik yönlerine odaklanmaktadır. Çalışma aynı zamanda bilgi teknolojisinin, eski ve yeni direniş yöntemlerini bir araya getirmeyi başaran yeni siyasal aktörlükleri şekillendirmedeki ve rejim kontrolü dışındaki siyasal etkileşim alanını genişletmedeki önemli rolünü ele almaktadır. Bu bağlamda, çalışma şu şekilde organize edilmiştir. İlk olarak, devlet ve devlet-toplum ilişkilerinin dönüşümü neoliberal siyasal dönüşüm kapsamında anlamlandırılmıştır. İkinci olarak, siyasetin, dayanışma ve bilgi ağlarının alternatif biçimlerini görmek için yönetilenlerin siyaseti ele alınmıştır. Üçüncü olarak, Arap dünyasında gerçekleştiren neoliberal reformların meşruiyet dayanağı olan mevcut toplumsal sözleşmenin altını oyduğu Mısır örneği üzerinden ele alınmıştır. Son olarak devletin politik-ekonomik krizi döneminde internetin yönetilenlerin siyaseti üzerindeki rolü analiz edilmiştir.Çalışma, devlet-toplum ilişkilerinin neoliberal dönüşümü ve siyasal aktivizmin alternatif mekânlarının Arap ayaklanmalarını açıklamada kapsamlı bir bakış açısın sunmaktadır.
Post-kolonyal toplumsal sözleşmeden Arap ayaklanmalarına: Devlet-toplum ilişkilerinin neoliberal dönüşümü ve yeni siyasal aktivizmin alternatif mekânlar
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Arab uprisings; legitimacy; neoliberalism; social contract; social media; Arap ayaklanmaları; neoliberalizm; sosyal medya; meşruiyet; toplumsal sözleşme